The Study Viscocity of Oil-in-Oil Emulsion with Different Surfactants - Pandey, I.P.; Sharma, Kanchan; Rawat, T.S. (Asian Journal of Chemistry, 2012)
In the present the work viscosity of oil-in-oil emulsion with different surfactants are reported.